STUDENTS IN TWO WORLDS: ANALYSIS OF CHARACTER DIFFERENCES IN ISLAMIC BOARDING SCHOOLS AND SOCIETY - Hudifaturrohmah, Hudifaturrohmah; Mufidah, Hilmy; Fadilah, Nurul; Hasanah, Uswatun; Sari, Cindy Eka Puspita; Agustina, Dyah Ayu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research analyzes the differences in the character of students in the Islamic boarding school environment and society. Islamic boarding schools as traditional Islamic educational institutions have a central role in forming the personality of students through the application of religious values, discipline and the habit of living a simple life. On the other hand, society has a more complex influence due to the diversity of values, extensive social interaction and the challenges of modernity. These environmental differences create dynamics in the students' thought patterns, behavior and adaptation when interacting outside the Islamic boarding school. The research results show that santri tend to maintain Islamic boarding school values in society, even though they experience several challenges in the consistency of their implementation. This research is expected to provide insight for Islamic boarding school managers, the community and policy makers to strengthen the synergy between Islamic boarding school values and the needs of modern society.